Structural Proteomics Methods to Interrogate the Conformations and Dynamics of Intrinsically Disordered Proteins - Beveridge, Rebecca; Calabrese, Antonio N. (Frontiers in Chemistry, 2021)
Intrinsically disordered proteins (IDPs) and regions of intrinsic disorder (IDRs) are abundant in proteomes and are essential for many biological processes. Thus, they are often implicated in disease mechanisms, including neurodegeneration and cancer. The flexible nature of IDPs and IDRs provides many advantages, including (but not limited to) overcoming steric restrictions in binding, facilitating post-translational modifications and achieving high binding specificity with low affinity. IDPs adopt a heterogeneous structural ensemble, in contrast to typical folded proteins, making it challenging to interrogate their structure using conventional tools. Structural mass spectrometry (MS) methods are playing an increasingly important role in characterising the structure and function of IDPs and IDRs, enabled by advances in the design of instrumentation and the development of new workflows, including in native mass spectrometry, ion mobility-MS, top down-MS, hydrogen-deuterium exchange-MS, crosslinking-MS and covalent labelling. Here we describe the advantages of these methods that make them ideal to study IDPs, and highlight recent applications where these tools have underpinned new insights into IDP structure and function that would be difficult to elucidate using other methods.